Analisis Produk Layanan Rumah Sakit dalam Lingkup Bauran Pemasaran - Rahmawati, Rahmawati (UI Scholars Hub, 2018)
Hospitals as large service institutions, are required to be able to fulfill public health services well, this is due to a lot of competition and if they do not pay attention to these demands, it will be difficult to maintain their survival. Some breakthroughs in health services are a necessity especially to bridge the level of social differences in health services on the one hand to find the right form of funding efficiency for the community on the other hand. For this reason, the hospital must be able to develop a marketing strategy through an effective and efficient marketing mix for the development of the hospital itself. In that context, the marketing mix becomes something that needs to be a concern so that the existence of hospitals is either business or non-business